PENGARUH SELF EFFICACY DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN PADA PT ANGKASA PURA I (PERSERO) BANDARA INTERNASIONAL I GUSTI NGURAH RAI – BALI - Ramadhan, Gilang; Setyowati, Trias; Winahyu, Pawestri (Growth, 2022)
Human resources are one of the most important assets for the company. The role of human resources for companies is not only seen in the results of work productivity but also seen in the quality of work produced. Employee performance is something that deserves important attention for the company. Employee performance is the main measure of organizational success, organizational goals are always trying to improve employee performance so that the company can achieve its vision and mission. One of the qualities of work that can improve employee performance is from improving self-efficacy and employee engagement. That way the performance of employees at PT Angkasa Pura I (Persero) I Gusti Ngurah Rai International Airport-Bali can increase. This study aims to analyze and determine the effect of self-efficacy and employee engagement on employee performance at PT Angkasa Pura I (Persero) I Gusti Ngurah Rai International Airport-Bali. This research technique uses causal analysis techniques with a quantitative approach. The population in this study were employees working at PT Angkasa Pura I (Persero) I Gusti Ngurah Rai International Airport-Bali. The sample used was PT Angkasa Pura I (Persero) I Gusti Ngurah Rai International Airport-Bali employees were taken as many as 85 employees using the cluster random sampling method. The analytical method used is descriptive statistics, instrument test (validity test and reliability test), multiple linear regression analysis, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), hypothesis test (t test), and coefficient of determination test ( R2) using the SPSS application. The results of this study indicate that self-efficacy has a positive effect on employee performance with a significance level of 0.047 <0.05. And employee engagement has a positive effect on employee performance with a significance level of 0.015 <0.05. These two variables have a positive and significant effect on employee performance at PT Angkasa Pura I (Persero) I Gusti Ngurah Rai International Airport-Bali.